A new methodology for the determination of material damping distribution based on tuning the interference of solid waves. (15th January 2015) - Kostka, Pawel; Holeczek, Klaudiusz; Hufenbach, Werner
Highlights: Presented concept of a method for damping distribution determination with theoretically unlimited spatial resolution for a given sensor network density. Validation of the underlying assumption that a standing wave can be considered as a weighting function, which determines the distribution of dissipated energy. Confirmation of the capabilities of the proposed method in analytical studies. Abstract: An inhomogeneous distribution of material damping is in most cases an effect of damage, such as is often caused by an impact event, persisting dynamic load or misuse. Typical methods for material damping determination, for example dynamical mechanical analysis or relaxation tests, are characterised by limited or zero spatial resolution which unavoidably results in the mis-estimation of the damping distribution. The new method presented in this paper gives theoretically unlimited spatial resolution by means of a very sparse array of stationary actuating/sensing elements. The proposed method relies on the assumption that a standing wave – originating from the interference between two counter-propagating waves – can be considered as a weighting function, for determining the distribution of dissipated energy. This assumption has been proven in analytic studies of a viscoelastic medium with different damping distributions and homogeneous stiffness distribution.